Calculation of the transient heat distribution on the plate by the finite element method - Turskienė, Sigita (Lietuvos matematikos rinkinys, 2001)
The paper deals with the analysis problem of transient heat distribution on the plate. The external surfaces of the plate are subject to the heat transfer by convection with time dependent fluid temperature. The efficiency of the numerical results is illustrated by the solution of the problem of a cooled plate.